1982
DOI: 10.1079/bjn19820019
|View full text |Cite
|
Sign up to set email alerts
|

The origin of urinary aromatic compounds excreted by ruminants 1. The metabolism of quinic, cyclohexanecarboxylic and non-phenolic aromatic acids to benzoic acid

Abstract: I . The contribution of dietary constituents to the large urinary output of benzoic acid characteristic of ruminants and some herbivores is not well understood.2. Methods for the analysis of quinic, cyclohexanecarboxylic, benzoic, phenylacetic, 3-phenylpropionic and cinnamic acids in urine and in rumen Huids were developed.3. The urinary output ofaromatic acids by sheep given seven rations was determined: benzoic acid output varied between 2.8 and 7.8 g/d; phenylacetic acid output between 0.16 and 1.3 g/d; cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…4c and d, with urines from the slaughtered animals containing lower amounts of hippuric acid and creatinine and higher amounts of phenylacetylglycine and p-cresol sulfate. Hippuric acid and phenylacetylglycine are glycine conjugates produced by the rumen microbiotic flora that display different concentration profiles depending on time since feeding (Martin 1982). Hence, the observed clustering is probably an effect of the practice of not feeding the animals on the morning before slaughter.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…4c and d, with urines from the slaughtered animals containing lower amounts of hippuric acid and creatinine and higher amounts of phenylacetylglycine and p-cresol sulfate. Hippuric acid and phenylacetylglycine are glycine conjugates produced by the rumen microbiotic flora that display different concentration profiles depending on time since feeding (Martin 1982). Hence, the observed clustering is probably an effect of the practice of not feeding the animals on the morning before slaughter.…”
Section: Resultsmentioning
confidence: 78%
“…At the vertex of the V-shaped trajectory, representing 6-month-old animals around puberty and at the termination of the differential postnatal feeding treatment, components related to ruminant microbiotic flora (Martin 1982), such as hippuric acid, phenylacetylglycine, and other aromatic compounds, start to appear albeit still at low levels. The aromatic constituents subsequently increase as the V-shaped trajectory reaches the opposite endpoint in the early adulthood at the age of 19 and 24 months, during which period all the animals were fed the same and exclusively grass-based diet.…”
Section: Resultsmentioning
confidence: 99%
“…The principal dietary precursors of benzoic acid are phenolic compounds that yield 3-phenylpropionic acid on microbial fermentation in the rumen (Martin, 1982). The urinary concentration of hippuric acid varies between 0.37 and 0.70 g N/l (Table 1).…”
Section: Urea In Urinementioning
confidence: 99%
“…When cinnamic acid was infused in the rumen or abomasum of ruminants, 70% was recovered in the urine as benzoic acid conjugates (Martin, 1982a). In the rumen, 3-phenylpropionic acid originated by microbial metabolism of hydroxycinnamic acids, is absorbed and oxidised in organism and eliminated as benzoic acid in urine (Martin, 1982b). Also in sheep, Pagella et al, 1997; showed that 3-phenylpropionic acid (oxidation product of the two CG 22 compounds 3-phenylpropanol and 3-phenylpropanal) infused in the rumen was excreted in the urine mainly as hippuric acid.…”
Section: Oxidative-and Phase II Metabolismmentioning
confidence: 99%